Effect of Heating Time on the Quality of Tapioca Starch and Xanthan Gum Mixture - Prawta Chantaro; Rungnaphar Pongsawatmanit (Agriculture and Natural Resources, 2010)
Heating is an important step for preparing starch-based products, as heating affects the quality of the products due to gelatinization and degradation of the starch. The effect of thermal treatment on the pasting properties of tapioca starch (TS) with and without xanthan gum (Xan) under constant shear was investigated using a rapid visco-analyzer (RVA). The freeze-thaw stability of the TS and TS/Xan pastes was also determined. Two mixtures of 5% (w/w) TS and TS/Xan (mixing ratio = 9/1) at pH 7 were assessed. Final viscosities decreased with heating time at 95°C. A longer heating time increased the breakdown of the gelatinized TS and TS/Xan mixtures (p<0.05). Substitution of Xan for TS depressed the setback of the TS pastes (p<0.05). Changes in viscosity values of both the TS and TS/Xan mixtures during heating at 95°C with a constant shear rate in the RVA profile exhibited a pseudo-first-order reaction with respect to heating time. From the repeated freeze-thaw treatments, the TS pastes containing Xan exhibited lower water separation compared with those of the TS pastes alone for the same heating time. The results may have important implications for industrial applications by improving the pasting properties and freeze-thaw stability of TS-based products.